2011
DOI: 10.1002/jsfa.4352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tea polyphenols on microbiological and biochemical quality of Collichthys fish ball

Abstract: The shelf life of Collichthys fish balls supplemented with tea polyphenols can be prolonged for an additional 6 days in good condition at 0 °C storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 24 publications
5
38
0
Order By: Relevance
“…The impact of TP may be attributed to the major components of TP, catechins, which have both antimicrobial and antioxidant activity (Almajano, Carbó, Jimenez, & Gordon, ). Similar results with the use of TP have been reported for fresh silver carp (Fan et al., ) and Collichthys fish balls (Yi et al., ). Importantly, the SA‐TP coating exhibited the strongest antimicrobial effects among all the treatment groups.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The impact of TP may be attributed to the major components of TP, catechins, which have both antimicrobial and antioxidant activity (Almajano, Carbó, Jimenez, & Gordon, ). Similar results with the use of TP have been reported for fresh silver carp (Fan et al., ) and Collichthys fish balls (Yi et al., ). Importantly, the SA‐TP coating exhibited the strongest antimicrobial effects among all the treatment groups.…”
Section: Resultssupporting
confidence: 87%
“…Yi et al. () observed that TP inhibited microbial development and an increase in TVB‐N in Collichthys fish balls stored at 0 °C storage, thus prolonging their shelf life for an additional 6 days. Lu et al.…”
Section: Resultsmentioning
confidence: 99%
“…For examples, dip treatment with 0.2% GTP was effective in inhibiting spoilage bacteria growth and extending the ice storage life of fish samples to 35 days compared to 28 days for the control group [3]. The total viable counts reduced two orders of magnitude in Collichthys fish balls supplemented with 0.25 g/kg GTPs compared with the controls [4]. GTPs were also used combined with other natural preservatives.…”
Section: Introductionmentioning
confidence: 99%
“…GTPs and EGCG have a broad antimicrobial spectrum and inhibit the growth of many foodborne pathogenic and spoilage bacteria [4, 11]. Several studies have indicated that the antibacterial activity of EGCG is due to damage to the bacterial cell membrane, such as peptidoglycan [12], outer membrane proteins [13] and lipid bilayers [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation